A two-phase possibilistic linear programming methodology for multi-objective supplier evaluation and order allocation problems - Ozgen, Dogan; Onut, Semih; Gulsun, Bahadir; Tuzkaya, Umut Rifat; Tuzkaya, Gulfem (ELSEVIER SCIENCE INC, 2008)
In this study, an integration of the analytic hierarchy process (AHP) and a multi-objective possibilistic linear programming (MOPLP) technique is developed to account for all tangible, intangible, quantitative, and qualitative factors which are used to evaluate and select suppliers and to define the optimum order quantities assigned to each. A multi-objective linear programming technique is first employed to solve the problem. To model the uncertainties encountered in the integrated supplier evaluation and order allocation methodology, fuzzy theory is adopted. Hence, possibilistic linear programming (PLP) is proposed for solving the problem, as it is believed to be the best approach for absorbing the imprecise nature of the real world. In the supplier evaluation phase, environmental criteria are also considered. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: supplier evaluation; order allocation; AHP; multi-objective possibilistic linear programming; VENDOR SELECTION PROBLEM; CAPACITY ALLOCATION; PERFORMANCE; SYSTEM; MODEL; Computer Science